Nodal deviation: its factors and manifestations from a Quranic perspective - misanjas, Mohamed Ismail Hashem / Ammar Bassem Saleh ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The research aims to study the internal factors that are positive for nodal deviation and result from the excessive and exaggerated tendency of love of the first life , where the deviant sees only what his devil says ; and this means to the immoral religion , based on possibilities and mental assumptions stemming from illusion and suspicion. The research also showed that external factors work to complete the straight intellectual of some people, and the aim of this is to push towards the acceptance of their corrupt religion , and it is striking that the sponsors of sedition have the insistence on deception, which makes them invent ideas commensurate with the need of each soul, so their weapon was that intellectual or military invasion; as well as tactical policies to get people out of the doctrine of integrity into the darkness of deviation. The research also presented the appearance of infidelity, is not manifested on the behavior of the individual, except after a complex conflict between the certainty in the knowledge of Allah and between doubts and suspicions based on superficial intellectual perceptions that are not based on any logic, but are based on false tendencies, desires and sensations in perception, which result in a doctrinal deviation, characterized by making God as enemy, his angels and apostles at all times , On many well-known ways , the most recent of which are satirical comics or cartoons (caricatures) offensive to the Prophet (peace and blessings of God be upon him), and others.